FACTORS INFLUENCING ASSAULT RIFLE SHOOTING - Popov, Georgi (Horizons - International Scientific Journal, 2021)
In the current military-political environment, the widespread use of nuclear, chemical and bacteriological weapons in the development of military conflicts is unlikely, as this would lead to the self-destruction of civilization. Modern local wars and armed conflicts are an increasingly common form of armed conflict between warring parties within a country. In the context of armed struggle without weapons of mass destruction, the decisive role will belong to conventional means.These are types of weapons that do not use chemicals, biological agents or nuclear reactions to destroy the target or inflict damage on an object. These include both small arms and artillery systems for area fire, high-precision weapons, tanks, and anti-tank weapons. An important place among them is occupied by small arms.